TAFSIR HERMENEUTIK DAN FENOMENOLOGI DALAM AL-QURAN - Zubairin, Ahmad (STAI Asy-Syukriyyah, 2022)
Al-Quran is the holy book of humanist Muslims. The entire content of the verse leads to humanizing humans, not the other way around. However, this noble goal has not been fully realized, it is allegedly by some circles because the methodology in the interpretation of the Qur'an still uses celestial language which is difficult to reason and apply. The interpreters of the Qur'an are still